Tax incentives for research and development and their use in tax planning - Olena Pfeiffer; Christoph Spengel (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2017)
This study provides a comprehensive analysis of various aspects of R&D tax incentives. It explains the economic justification behind the state support of research and development and summarizes its main types. In addition, it gives an overview of the existing R&D tax incentives in Europe and provides a thorough review of the empirical literature on the outcomes of fiscal incentives. Furthermore, the Devereux and Griffith model is used to determine the effective tax burden of multinational firms that reside in countries which implement R&D tax support and countries which do not. The model is developed further following Spengel and Elschner (2010) and Evers et al. (2015) to reflect a potential use of R&D tax incentives by multinational firms for tax planning. The hypothesis developed in the model is tested in an empirical estimation, where we employ the OECD data on international co-operation in patents. According to our main findings, there are at least two reasons why input-oriented R&D tax incentives, such as tax credits and tax super-deductions, constitute a more suitable instrument for fostering research and development than the output-oriented incentives, such as IP Boxes. First, there is robust evidence found in the empirical literature which shows the positive effect introducing input-oriented tax incentives has on a firm's innovative activity, whereas studies on output-oriented tax incentives are not able to support this argument. Secondly, according to our theoretical and empirical analyses, output-oriented R&D tax incentives may be used by multinationals for tax planning as opposed to their intended use of fostering research and development.
urn:nbn:de:bsz:180-madoc-436341
Keywords: H25; F23; H26; H3; 330; research and development; R&D; tax planning; corporate taxation